2010
DOI: 10.1161/circoutcomes.109.864447
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Not Associated With Increased Mortality or Cardiovascular Risk in Nondiabetic Patients With a New Diagnosis of Coronary Artery Disease

Abstract: Background-Metabolic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…It has also been suggested that hyperglycemia per se, more than the metabolic syndrome as an entity, predicts the prognosis and outcome in CVD [7], [18], [24], [25], [26], and that young women are especially prone to the negative effects of both [27]. The present study shows that FMD was lower and prevalence of ED was higher in women with hyperglycemia.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has also been suggested that hyperglycemia per se, more than the metabolic syndrome as an entity, predicts the prognosis and outcome in CVD [7], [18], [24], [25], [26], and that young women are especially prone to the negative effects of both [27]. The present study shows that FMD was lower and prevalence of ED was higher in women with hyperglycemia.…”
Section: Discussionsupporting
confidence: 54%
“…Our findings support the notion that endothelial dysfunction is an important mechanism of gender-specific effects on CVD in patients with the metabolic syndrome, hyperglycemia or diabetes mellitus. Furthermore, the metabolic syndrome used as an entity may mask important differences in the sensitivity to specific risk factors, especially hyperglycemia, in assessing health and mortality [24], [25], [32].…”
Section: Discussionmentioning
confidence: 99%
“…While there is some evidence of an increased risk in the stable coronary artery disease population,(1) this was mostly observed in patients with concomitant diabetes. (10) Our study shows that the diagnosis of MetS made in the setting of an AMI also confers a poor prognosis, independent of diabetes.…”
Section: Discussionmentioning
confidence: 63%
“…Some authors have raised the question of whether it has additive prognostic value for CAD in tandem with its individual components. It was suggested that attempts to define a criteria of the MetS that simultaneously predicts for CAD and diabetes are unhelpful because the MetS had weak or no association with cardiovascular risk (6, 10, 18, 19). Those findings indicated that the MetS is a marker of CAD risk, but not above and beyond the risk associated with its individual components.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the MetS has come to the fore as a major risk factor of CAD (3, 4). Isomaa et al (5) reported that patients with the MetS had a higher incidence of CAD and increased all-cause mortality than those without it, but other researchers failed to verify these relationships (6, 7). Thus, unlike diabetes mellitus, which is a well-known established risk factor for CAD (8, 9), whether MetS has an additive impact on the development of CAD in addition to its individual components (e.g., hypertension, diabetes) is controversial (10).…”
Section: Introductionmentioning
confidence: 99%